Effect of Diet Enriched With Hemp Seeds on Goat Milk Fatty Acids, Transcriptome, and miRNAs - Cremonesi, Paola; Capra, Emanuele; Turri, Federica; Lazzari, Barbara; Chessa, Stefania; Battelli, Giovanna; Colombini, Stefania; Rapetti, Luca; Castiglioni, Bianca (Frontiers in Animal Science, 2022)
In dairy ruminants, a diet supplemented with feed rich in unsaturated fatty acids can be an effective medium to increase the health-promoting properties of milk, although their effect on the pathways/genes involved in these processes has not been properly and completely defined to date. To improve our knowledge of the cell’s activity in specific conditions, next-generation RNA-sequencing technology was used to allow whole transcriptome characterization under given conditions. In addition to this, microRNAs (miRNAs) have recently been known as post-transcriptional regulators in fatty acid and cholesterol metabolism by targeting lipid metabolism genes. In this study, to analyze the transcriptome and miRNAs in goat milk after a supplemental diet enriched with linoleic acid (hemp seeds), next-generation RNA-sequencing was used in order to point out the general biological mechanisms underlying the effects related to milk fat metabolism. Ten pluriparous Alpine goats were fed with the same pretreatment diet for 40 days; then, they were arranged to two dietary treatments consisting of control (C) and hemp seed (H)-supplemented diets. Milk samples were collected at 40 (time point = T0) and 140 days of lactation (time point = T1). Milk fatty acid (FA) profiles revealed a significant effect of hemp seeds that determined a strong increment in the preformed FA, causing a reduction in the concentration of de-novo FA. Monounsaturated and polyunsaturated n−3 FAs were increased by hemp treatment, determining a reduction in the n−6/n−3 ratio. After removing milk fats and proteins, RNA was extracted from the milk cells and transcriptomic analysis was conducted using Illumina RNA-sequencing. A total of 3,835 genes were highly differentially expressed (p-value < 0.05, fold change > 1.5, and FDR < 0.05) in the H group. Functional analyses evidenced changes in metabolism, immune, and inflammatory responses. Furthermore, modifications in feeding strategies affected also key transcription factors regulating the expression of several genes involved in milk fat metabolism, such as peroxisome proliferator-activated receptors (PPARs). Moreover, 38 (15 known and 23 novel) differentially expressed miRNAs were uncovered in the H group and their potential functions were also predicted. This study gives the possibility to improve our knowledge of the molecular changes occurring after a hemp seed supplementation in the goat diet and increase our understanding of the relationship between nutrient variation and phenotypic effects.